2022
DOI: 10.1161/jaha.121.025629
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Cerebral Phenotypes Associated With Monogenic Cerebral Small‐Vessel Disease

Abstract: Background Cerebral small‐vessel disease (cSVD) is an important cause of stroke and vascular dementia. Most cases are multifactorial, but an emerging minority have a monogenic cause. While NOTCH3 is the best‐known gene, several others have been reported. We aimed to summarize the cerebral phenotypes associated with these more recent cSVD genes. Methods and Results We performed a syst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Radiologic hallmarks of CARASIL include high-signal-intensity lesions in the periventricular and deep white matter and multiple lacunar infarcts in the basal ganglia and the thalamus, but the superficial white matter is generally spared ( 11 ). Whittaker et al ( 12 ) have also reported that microbleeds are mostly found in the deep white matter of the brain in patients with heterozygous HTRA1 mutations. Our findings are consistent with the results of the above studies, in that both of these patients had diffuse WMLs and chronic microbleeds in the deep white matter and lacunar infarcts in the basal ganglia and the corona radiata.…”
Section: Discussionmentioning
confidence: 97%
“…Radiologic hallmarks of CARASIL include high-signal-intensity lesions in the periventricular and deep white matter and multiple lacunar infarcts in the basal ganglia and the thalamus, but the superficial white matter is generally spared ( 11 ). Whittaker et al ( 12 ) have also reported that microbleeds are mostly found in the deep white matter of the brain in patients with heterozygous HTRA1 mutations. Our findings are consistent with the results of the above studies, in that both of these patients had diffuse WMLs and chronic microbleeds in the deep white matter and lacunar infarcts in the basal ganglia and the corona radiata.…”
Section: Discussionmentioning
confidence: 97%
“…Pathway analyses highlight ECM structure and function, known to play an important role in cSVD 5 , 20 , 21 , and several loci include genes involved in the matrisome (ECM and associated proteins), perturbations of which were proposed as a convergent pathologic pathway in cSVD ( LAMC1 , EFEMP1 , COL4A2 , SH3PXD2A , VWA2 ) 5 , 21 . Several PVS risk loci (at FOXF2 , EFEMP1 , KCNK2 and NBEAL1-ICA1L ) are known risk loci for other cSVD features (WMH, SVS) 5 , 22 , 23 , and mutations in two MTAG genes cause monogenic SVD (at COL4A1-COL4A2 and STN1 ) 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…51 In a subset of patients, brain calcifications, schizencephaly, and cerebellar atrophy have been found. 49 Patients with all the subtypes of HCHWA develop a neuroimaging picture which resembles that of the sporadic forms of CAA. Besides periventricular and/or subcortical WMHs, hemorrhages in different stages of evolution are commonly found.…”
Section: Continuedmentioning
confidence: 99%
“…19,48 Unlike patients with COL4A2 mutations, a variable degree of brain atrophy is described in those affected by COL4A1 -related CSVD, with rare involvement of corpus callosum. 48,49 In subjects with the HANAC syndrome, WMHs can be periventricular, subcortical, and/or subtentorial, involving the centrum semiovale, internal and external capsules, frontal and parietal lobes, and, rarely, the pons, but sparing the posterior cerebral regions. 50 A specific additional MRI element of COL4A1 -related CSVD and HANAC syndrome is represented by intracranial aneurysms, which are often asymptomatic, multiple in up to 50% of patients and mainly involve intracranial carotid (as in HANAC) and middle cerebral and basilar arteries.…”
Section: Clinical-neuroimaging Features Of Monogenic Csvdmentioning
confidence: 99%
See 1 more Smart Citation